A randomized phase 2b trial of baricitinib, an oral Janus kinase (JAK) 1/JAK2 inhibitor, in patients with moderate‐to‐severe psoriasis. (5th April 2016) - Papp, K.A.; Menter, M.A.; Raman, M.; Disch, D.; Schlichting, D.E.; Gaich, C.; Macias, W.; Zhang, X.; Janes, J.M.
Summary: Background: Plaque psoriasis is a chronic and often debilitating skin disorder and proinflammatory cytokines are known to play a key role in the disease process. Objectives: To evaluate the safety and efficacy of baricitinib, an oral Janus kinase (JAK) 1/JAK2 inhibitor, in patients with moderate‐to‐severe psoriasis in a randomized, double‐blind, placebo‐controlled, dose‐ranging phase 2b study. Methods: Patients were randomized ( n = 271) to receive placebo or oral baricitinib at 2, 4, 8 or 10 mg once daily for 12 weeks (Part A). Dose adjustment for 12 additional weeks was based on percentage improvement in the Psoriasis Area and Severity Index (PASI) score. The primary end point was Psoriasis Area and Severity Index (PASI) 75% (PASI‐75) at 12 weeks for North American patients ( n = 238); secondary end points were safety and efficacy measures in the entire population. Results: At week 12, more North American patients in the 8‐mg (43%) and 10‐mg (54%) baricitinib groups than in placebo group (17%; P < 0·05) achieved PASI‐75. All baricitinib‐treated groups had greater mean changes from baseline in their PASI scores ( P < 0·05) at 12 weeks and (except 2 mg) had higher rates of PASI‐50 than the placebo group; statistically significant PASI‐90 responses were achieved in the 8‐mg and 10‐mg groups at 8 and 12 weeks. More than 81% of PASI‐75 responders maintained their scores through 24 weeks. During Part A, study discontinuations due to adverse events (AEs) were 0%, 0%, 2·8%, 6·3% and 5·8% and treatment‐emergent AE rates were 44%, 50%, 47%, 58% and 64% for placebo and 2‐, 4‐, 8‐ and 10‐mg baricitinib groups, respectively. No opportunistic infections were observed in any treatment group. Dose‐dependent changes in laboratory values were observed. Conclusions: Patients with moderate‐to‐severe psoriasis treated with baricitinib for 12 weeks achieved significant improvements in PASI‐75. Abstract : What's already known about this topic? Psoriasis is a common, chronic, immune‐mediated inflammatory skin disease. Key cytokines involved in the pathogenesis of psoriasis use the Janus kinase–signal transducer and activator of transcription (JAK‐STAT) pathway. New safe and effective therapies are needed for patients. What does this study add? Baricitinib, a selective JAK1/JAK2 inhibitor, demonstrates clinical efficacy in the treatment of psoriasis. Baricitinib was well tolerated over the 24‐week trial period. Linked Comment: Albrecht and Gerdes. Br J Dermatol 2016; 174: 1183–1184 .